2015
DOI: 10.1104/pp.15.00242
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy Supports Biomass Production and Nitrogen Use Efficiency at the Vegetative Stage in Rice

Abstract: Much of the nitrogen in leaves is distributed to chloroplasts, mainly in photosynthetic proteins. During leaf senescence, chloroplastic proteins, including Rubisco, are rapidly degraded, and the released nitrogen is remobilized and reused in newly developing tissues. Autophagy facilitates the degradation of intracellular components for nutrient recycling in all eukaryotes, and recent studies have revealed critical roles for autophagy in Rubisco degradation and nitrogen remobilization into seeds in Arabidopsis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
92
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(104 citation statements)
references
References 45 publications
6
92
0
3
Order By: Relevance
“…We recently showed in Arabidopsis that autophagy is important for nitrogen use efficiency and especially for the remobilization of nitrogen from the rosette leaves to the seeds [18,19]. Similar features were demonstrated in maize [20] and there are several lines of evidence that autophagy also plays a role for nitrogen recycling in rice [21] In addition, Masclaux-Daubresse et al [24] also showed that autophagy is globally important for metabolic and redox homeostasis in the leaves, especially under nitrate limitation. Links between autophagy, redox and stress resistance have been described in Arabidopsis in several reports [39][40][41][42][43] and autophagy also seems involved in plant immunity [44,45].…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…We recently showed in Arabidopsis that autophagy is important for nitrogen use efficiency and especially for the remobilization of nitrogen from the rosette leaves to the seeds [18,19]. Similar features were demonstrated in maize [20] and there are several lines of evidence that autophagy also plays a role for nitrogen recycling in rice [21] In addition, Masclaux-Daubresse et al [24] also showed that autophagy is globally important for metabolic and redox homeostasis in the leaves, especially under nitrate limitation. Links between autophagy, redox and stress resistance have been described in Arabidopsis in several reports [39][40][41][42][43] and autophagy also seems involved in plant immunity [44,45].…”
Section: Discussionmentioning
confidence: 68%
“…Arabidopsis thaliana wild type (Col-0), the atg5 mutant (SAIL_129B07) and the complemented atg5 p35S::HvATG5 mutant (this work) were grown on soil in either a glasshouse or a growth chamber at 60% relative humidity with a 16/8 light/dark cycle at 21 …”
Section: Plant Materials and Growth Conditionsmentioning
confidence: 99%
See 2 more Smart Citations
“…), despite removal of the exogenous N supply, new leaves continued to be produced using N remobilized from older organs [46]. Although some loss of N must be expected in senescent biomass, N remobilization is clearly important in determining plant productivity, with a recent paper demonstrating significantly reduced growth in mutant rice plants with reduced capacity for Rubisco degradation, particularly under N limiting conditions [47]. Thus, we can postulate an optimal leaf protein turnover rate which maximises canopy rather than leaf photosynthesis.…”
Section: Plant Morphology As a Partial Consequence Of Photosynthetic mentioning
confidence: 99%